Apical periodontitis in osteoporotic postmenopausal women: Systematic review and meta-analysis - Areal-Quecuty, Victoria; Cantiga-Silva, Cristiane [UNESP]; Simón-Soro, Aurea; Cabanillas-Balsera, Daniel; Martín-González, Jenifer; Saúco-Márquez, Juan J.; Segura-Egea, Juan J. (Medicina Oral, S.L., 2024)
Background: The aim of this systematic review and meta-analysis was to analyze the scientific evidence about the association between osteoporosis in postmenopausal women and the prevalence of apical periodontitis, assessed radiographically. Material and Methods: PRISMA Guidelines have been followed. The research question was: In adult women, does the presence or absence of osteoporosis affect the prevalence of AP, radiographically diagnosed? A systematic search was performed in PubMed/MEDLINE, Web of Science, Scopus and EMBASE. The meta-analyses were calculated with the Open Meta Analyst software. Risk of bias was assessed using the Newcastle Ottawa Scale. The certainty of evidence was assessed by GRADE. Results: Four studies were selected. Meta-analysis showed an overall OR = 2.2 (95% CI = 0.94-4.97; p = 0.07), indicating that osteoporotic women had approximately twice the probability of having periapical lesions, compared to control women, although the difference was only marginally significant. The overall risk of bias of the included studies was moderate, and the certainty of evidence was low. Conclusions: Apical periodontitis, assessed as periapical lesion, is more frequently diagnosed in osteoporotic women, who are twice as likely to have periapical radiolucent lesions.
Keywords: Apical periodontitis; endodontic medicine; menopause; meta-analysis; older adults; osteoporosis; postmenopausal women; systematic review